Imaging of Meningitis and Meningoencephalitis in Children - Kara, Simay A.; Choudhary, Gagandeep; Udayasankar, Unni K. (Journal of Pediatric Neurology, 2017)
Although central nervous system infections in children are rare, when suspected, urgent diagnosis and treatment are mandated to prevent morbidity and mortality. Inflammation of the meninges alone is termed meningitis; associated involvement of the underlying brain leads to meningoencephalitis. CSF analysis remains the gold standard in identifying the infectious agent. Imaging plays a vital role not only in supporting the diagnosis of meningitis or meningoencephalitis but also in identifying potential complications, monitoring treatment response, and follow-up. The pattern of meningeal and brain involvement can vary depending on the infectious agent; cerebral convexity meninges is commonly involved in acute bacterial infection, basilar meninges in tuberculosis, and meningoencephalitis in viral infection. In this article, we review the characteristic imaging appearances of common bacterial, mycobacterial and viral agents, role of newer imaging technique, and list potential complications.
Keywords: meningitis; cerebrospinal fluid; subarachnoid space; subdural effusion; empyema